Hi there! Have questions about your homework? At Brainly, there are 60 million students who want to help each other learn. Questions are usually answered in less than 10 minutes. Try it for yourself by posting a question! :D

Hi there! Have questions about your homework? At Brainly, there are 60 million students who want to help each other learn. Questions are usually answered in less than 10 minutes. Try it for yourself by posting a question! :D

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.

Log (az - 1 ) = x + a y + b a z - 1 = exp (x+ ay + b) taking partial differentials a dz = exp (x + a y + b) . [dx + a dy]

a dz = exp(x+ay+b) [ dx + a dy ] = (az -1) [ 1 +a dy/dx] a dz / (a z - 1) = 1 dx + a dy or a/(az-1) dz/dx = 1 + a dy/dx

Log(az-1)=x+ay+b. Differentiating partially with respect to x and y we get 1 / az-1 * ap = 1 ——->(1)
1 / az-1 * ap = a ——->(2)
Dividing (2) by (1) we get q/p = a From equation (1) ap = az-1 a(z-p) = 1
q(z-p) =p
Answer :q(z-p)=p